From a virgin womb : the Apocalypse of Adam and the virgin birth - Welburn, Andrew J. (Biblical Interpretation Series, 2008)
Scholarly researches on the virgin birth have often focussed rather narrowly on the theological and historical difficulties it tends to raise. The Nag Hammadi Apocalypse of Adam, however, provides for the first time a glimpse into the wider background of ideas and myths to which it belonged. Prophecies there concerning a universal 'Illuminator' mention his birth 'from a virgin womb'. Several of the stories, drawn from Iranian and other sources , also appear in apocalyptic and testamental literature contemporary with Christian origins. The book centrally analyses a body of extraordinarily detailed narrative parallels between a cluster of stories in the Apocalypse and the infancy narratives of Mt. 1-2, concluding that these stories serve to identify Jesus as the True Prophet who is the fulfilment of history - though not as Son of God. The question of Mt.'s special tradition and its relation to Lk. is also cast in a new light.